Levels of Community Participation in Managing the Sumringah Waste Bank in Ngampelsari Village: Tingkat Partisipasi Masyarakat dalam Pengelolaan Bank Sampah Sumringah di Desa Ngampelsari - Winarti, Winarti; Mursyidah , Lailul (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Waste management remains a pressing environmental issue in urbanizing rural communities. Specific Background: The Sumringah Waste Bank in Ngampelsari Village, Sidoarjo Regency, has operated for nearly a decade as a community-based recycling initiative. Knowledge Gap: Despite its longevity, participation levels remain low, limiting the program’s environmental and economic benefits. Aims: This study explores community participation across decision-making, implementation, utilization, and evaluation stages in the Sumringah Waste Bank management. Results: Using a descriptive qualitative approach through interviews, observation, and documentation, the findings show low involvement in decision-making, moderate participation in implementation by active members, limited benefit utilization, and minimal engagement in evaluation processes. Novelty: The study provides an in-depth local analysis of community-based waste management using Cohen and Uphoff’s four-stage participation framework. Implications: Strengthening education, institutional support, and transparent evaluation mechanisms are necessary to foster inclusive and sustainable waste management in rural Indonesia. Highlights:• Community participation remains limited at all stages• Decision-making dominated by management• Need for stronger education and feedback channels